The long game : a Fixer novel - Barnes, Jennifer (Jennifer Lynn) (Bloomsbury Children's Books, 2016)
Tess Kendrick, a junior at the elite Hardwicke School in Washington D.C., can fix just about any problem her classmates--or their power-wielding parents--might have, but when terrorism, assassination, and murder strike, she soon finds herself wrapped up in an intricate plot that may end up hitting closer to home than she could have ever imagined.